Türkiye’de Kütüphanecilik Arşivcilik ve Dokümantasyon- Enformasyon Anabilim Dallarının/Bölümlerin'in Tercih Edilme Eğilimleri: 1988-1991 - Bülent Yılmaz (Türk Kütüphaneciliği)
In Turkey, opening of Archive Studies and Documentation-Information fields in the depermants of Librarianship has affected the choices of students at the university entrance examinations. In this study the ratio of choices amongst these three fields, and the number of students enrolled in each field have been investigated comparing the four universities which offer courses in these fields. There has been a decline in the choice of librarianship. The most favoured field is Documentation- Information. However, students’ prime concern is to enter the university with the points they expect to get rather than making a choice based on their interests. Thus they join these branches just to have a university degree in most cases. With these findings, the following were suggested: (1) the same type of points, and prefeence percentages should be used in all these fields; (2) considering the heavy use of technology in these professions, points taken in maths, science or Turkish & maths should be evaluated as opposed to social sciences or Turkish & social sciences; (3) the conditions should be changed in such a way that examination management will decraase the number of students to be enrolled and the percentages of preference; (4) improvement of the course programmes; (5) informing the candidates of the nature of the programmes before they make their choices.